Harnessing diversity in durum wheat (Triticum turgidum L.) to enhance climate resilience and micronutrient concentration through genetic and agronomic biofortification - Melash, Anteneh Agezew; Vad, Attila; Bytyqi, Bekir; Éva Babett Ábrahám (Acta Agraria Debreceniensis, 2022)
Huge consumption of wheat-driven food products with low bioavailability and small concentrations of zinc is responsible for zinc-induced malnutrition and associated health complications. The contemporary durum wheat varieties have inherently tiny zinc concentrations in developing grain, which cannot meet the daily human zinc demand. Despite the fact that over two billion people are suffering from iron and zinc-induced malnutrition, various intervention measures have been deployed to reverse the effect of zinc-induced malnutrition on humans. There are evidences that agronomic and genetic biofortification approaches can increase grain yield and nutritional quality (i.e. zinc, iron, protein, and vitamins) of durum wheat to a greater extent. However, there is a lack of direct empirical evidence for which the influence of both biofortification approaches on improving human health. Application of micronutrient-containing fertilizers either in the soil or foliarly is effective in combination with NPK, organic fertilizers coupled with efficient durum wheat varieties, emphasizing the need for integrated soil fertility management (ISFM). Although genetic biofortification is a cost-effective and sustainable approach, agronomic biofortification provides an immediate and effective route to enhancing micronutrient concentrations in durum wheat grain. The application of zinc-containing fertilizers is more effective under drought conditions than in normal growing situations. Hence, this article provides a key information for agronomists and breeders about the potential of biofortification interventions to improve durum wheat yield and enrich the grain qualitative traits to ensure food and nutritional security of the ever-increasing world population.